Evaluation of aflatoxin contamination in protein-rich pulses using a GFP-expressing Aspergillus flavus strain - Branstad-Spates, Emily H.; Sickler, Christine M.; Lebar, Matthew D.; Carter-Wientjes, Carol; Rajasekaran, Kanniah (Frontiers in Microbiology, 2025)
BackgroundMycotoxigenic fungi pose significant threats to food safety and marketability. Crop-specific differences in susceptibility to these fungi can influence contamination levels.ObjectivesThe resistance or susceptibility of protein-rich pulse crops—chickpeas (Cicer arietinum L. cv. CDC Frontier), lentils (Lens culinaris Medik cv. Eston), peas (Pisum sativum L. cv. LeRoy), and corn (Zea mays L. cv. H97C) to infection by Aspergillus flavus were evaluated using a kernel screening assay (KSA).MethodologyA. flavus strain 70 (AF-70) expressing green-fluorescent protein (GFP) was used to quantify fungal spread and mycotoxin production. Fungal infection and toxin levels, including aflatoxins (AFB1, AFB2), cyclopiazonic acid (CPA), and α-aflatrem, were monitored at 2-day intervals over a 10-day period post inoculation.ResultsAlthough all seeds were infected by A. flavus, corn produced significantly higher levels of AFB1 and AFB2 compared to pulses. However, pulses accumulated relatively higher levels of CPA and α‑aflatrem.ConclusionWhile pulses may be less susceptible to aflatoxin contamination than corn, the elevated concentrations of CPA and α‑aflatrem underscore the need for further toxicological evaluation and mechanistic studies. Future research should explore the underlying resistance mechanisms from field to storage to better ensure crop safety.